REVERSIBLE ANTERIOR CORD SYNDROME DUE TO PENETRATION OF THE SPINAL-CANAL BY PEDICULAR SCREWS - (:unkn) unknown (STOCKTON PRESS, 1995)
The use of transpedicular screws in patients with disturbed posterior column anatomy is sometimes hazardous. We report a patient with a burst fracture at T7 who developed an anterior cord syndrome immediately after posterior instrumentation. Diagnosis of the anterior cord syndrome was ascertained by an emergency computerised tomogram which showed a misplaced screw compressing the cord from the anterolateral aspect of the spinal canal. Extraction of this screw and revision of the instrumentation resulted in speedy and complete resolution of the neurological deficit. The patient was mobilised within the first postoperative week and was able to work by the fourth postoperative month. The application of smooth contoured screws and blunt surgical instruments was found to be helpful because they are less likely to produce a cutting injury of neural tissue. We must further stress that transpedicular screws for the upper thoracic segments are to be employed very cautiously, if ever, to avoid severe neurological complications.
Keywords: ANTERIOR CORD SYNDROME; SPINAL INSTRUMENTATION; PEDICULAR SCREW; COMPLICATIONS